Collaborative strategy for obtaining opinions on regional financial reports in the North Sulawesi provincial government - Arter Sendow; Nurliah Nurdin; Marja Sinurat (Sean Institute, 2024)
The preparation and examination of government financial reports are crucial tasks to be carried out and scrutinized by authorized state institutions to prevent financial mismanagement. After the examination, an opinion on the financial report will be issued. The research method employed by the researcher is qualitative, involving 12 informants. Data collection techniques, as proposed by Creswell, include observation, interviews, documentation, and audio-visual materials. Data analysis is conducted using SWOT analysis. The results of the analysis and discussion conducted by the researcher during the study reveal several factors contributing to the suboptimal collaboration, which poses a hindrance to maintaining an unqualified opinion without any reservations. These factors include recurring notes from external parties, uneven task distribution, insufficient budget, and an inadequate number of employees